Pemaafan Pada Penyintas Kekerasan Seksual Dalam Berpacaran Ditinjau Dari Big-Five Personality - Arthur Huwae (JURNAL PSIKOLOGI, 2021)
ABSTRACT            Sexual abuse in relationship often occurs and does much harm to woman as a victim. This condition is one of the cases in which victims suffer extreme physical, psychological, and social suffering, and not even a few end up in death. To recover from the bad story, an individual needs to have and shape a good personality so as to direct his or her use of the full forgiveness of the perpetrator, making his or her life more meaningful. Follow up on the problem, so it aims to know the attachment of the big five personalities to the victims. The methods of this study quantitative correlation that involves 48 participants, using an purposive sampling technique. Data gathering used the big five inventory scale and the forgiveness of sexual assault on relationship scale. Data analysis shows you were present positive relationship significant with an r-value at 0,850 and sig. 0,000 (p<0,01), which means ahypothesis is accepted. To feel calm, safe, and comfortable ,the victim is able to forgive and make peace with this bad story of dating and learn to keep up the good relationship with the perpetrator, even the victim learns to perform the positive act of helping the perpetrator. This allows the victim to achieve optimum psychological recovery.   Keywords: Forgiveness, Bigfive Personality, Young and Young, Sexual Abuse in RelationshipABSTRACT            Sexual abuse in relationship often occurs and does much harm to woman as a victim. This condition is one of the cases in which victims suffer extreme physical, psychological, and social suffering, and not even a few end up in death. To recover from the bad story, an individual needs to have and shape a good personality so as to direct his or her use of the full forgiveness of the perpetrator, making his or her life more meaningful. Follow up on the problem, so it aims to know the attachment of the big five personalities to the victims. The methods of this study quantitative correlation that involves 48 participants, using an purposive sampling technique. Data gathering used the big five inventory scale and the forgiveness of sexual assault on relationship scale. Data analysis shows you were present positive relationship significant with an r-value at 0,850 and sig. 0,000 (p<0,01), which means ahypothesis is accepted. To feel calm, safe, and comfortable ,the victim is able to forgive and make peace with this bad story of dating and learn to keep up the good relationship with the perpetrator, even the victim learns to perform the positive act of helping the perpetrator. This allows the victim to achieve optimum psychological recovery.  Keywords: Forgiveness, Bigfive Personality, Young and Young, Sexual Abuse in Relationship